Temporal and joint associations of hypertension and estimated pulse wave velocity with incident cardiovascular diseases: a population-based cohort study - Jiajia Zhang; Xiuqin Jia; Haibin Li; Qi Yang (European Journal of Medical Research)
Abstract Background Arterial stiffening and hypertension are interrelated, age-associated risk factors for cardiovascular disease (CVD). This study used estimated pulse wave velocity (ePWV), a recognized but non-standardized arterial stiffness measure, to investigate the temporal sequence of arterial stiffening and hypertension, and their mediating pathway and combined effects on CVD. Methods Data were drawn from the 2011–2018 China Health and Retirement Longitudinal Study. CVD was defined as self-reported physician-diagnosed heart disease and/or stroke. Elevated arterial stiffness was identified as ePWV ≥ the wave-specific median value, and hypertension as blood pressure ≥ 140/90 mmHg, current antihypertensive medication use, or a self-reported history. Cross-lagged panel analysis and mediation analysis, and modified Poisson regression were conducted on 6868 and 10,812 participants, respectively. Results The cross-lagged path coefficient from 2011 hypertension to 2015 elevated ePWV (β = 0.19, 95% CI = 0.15–0.22) was significantly greater than that from 2011 elevated ePWV to 2015 hypertension (β = 0.15, 95% CI = 0.11–0.20; P for difference = 0.007). Mediation analysis revealed an indirect association between 2011 hypertension and 2018 CVD through 2015 elevated ePWV (proportion mediated = 26.2%). Compared to normotension and normal ePWV, CVD risk was higher in those with elevated ePWV alone (RR = 1.28, 95% CI = 1.09–1.50), hypertension alone (RR = 1.39, 95% CI = 1.16–1.67), and both conditions (RR = 1.59, 95% CI = 1.39–1.82). Conclusions Hypertension likely precedes elevated ePWV, and this temporal relationship contributes to CVD progression. Individuals with hypertension and elevated ePWV had higher risks than those with either condition alone. Managing both hypertension and arterial stiffening may effectively reduce CVD risk, and ePWV could be a promising marker of arterial stiffness, especially in resource-limited settings. Graphical abstract Hypertension appeared to precede elevated estimated pulse wave velocity (ePWV), and elevated ePWV partially mediated the longitudinal hypertension-CVD association. Individuals with both hypertension and elevated ePWV had the highest CVD risk. CHARLS, China Health and Retirement Longitudinal Study; ePWV, estimated pulse wave velocity; CVD, cardiovascular diseases.